Efficacy of neoadjuvant cetuximab alone or with platinum salt for the treatment of unresectable advanced nonmetastatic cutaneous squamous cell carcinomas. (8th August 2015) - Reigneau, M.; Robert, C.; Routier, E.; Mamelle, G.; Moya‐Plana, A.; Tomasic, G.; Mateus, C.
Summary: Background: Refractory locally advanced or metastatic nonmelanoma skin cancer (NMSC) is a frequent therapeutic impasse. Objectives: To address the question of the efficacy of induction therapy with cetuximab as neoadjuvant treatment for locally advanced NMSC. Methods: From 2008 to 2013, all patients with a diagnosis of unresectable locally advanced skin squamous cell carcinoma were treated with neoadjuvant cetuximab alone (CM) or combined with a platinum salt and 5‐fluorouracil (CC). Resectability, and clinical and pathological response, as well as relapse‐free and overall survival were evaluated. Results: Thirty‐four patients, with a median age of 74·5 years, were evaluated. Twenty‐five patients received CC. After three cycles of CC, 23 of 25 patients whose tumours were initially unresectable became amenable to surgery (92%). A complete histological response was observed in 15 (65%) patients. The mean progression‐free and mean overall survival in operated patients were 8·5 and 26·0 months, respectively. Conclusions: There was a good response in terms of resectability and tumour control in the majority of patients, with few relapses, despite the initially poor prognosis of these tumours in this elderly group of patients. However, this therapeutic strategy needs to be validated in a prospective, randomized study. Abstract : What's already known about this topic? Refractory locally advanced or metastatic nonmelanoma skin cancer is a frequent therapeutic impasse. Chemotherapy [platin ± 5‐fluorouracil (5‐FU)] and radiotherapy are commonly used mostly as palliative treatment, either separately or combined. Cetuximab has been reported to be efficient in the treatment of some cases of cutaneous squamous cell carcinoma (SCC); however, local or distant recurrences are frequently observed after discontinuation or after several months of treatment. What does this study add? Neoadjuvant chemotherapy with cetuximab combined with platinum salt and 5‐FU or alone is a reasonable option in locally advanced cutaneous SCC. Tolerability is acceptable.